HIV and Menopause: A Systematic Review of the Effects of HIV Infection on Age at Menopause and the Effects of Menopause on Response to Antiretroviral Therapy - Kentaro Imai; Madeline Y. Sutton; Rennatus Mdodo; Carlos del Rio (Obstetrics and Gynecology International)
More than half of persons living with HIV infection in the United States (U.S.) will be ≥50 years of age by 2020, including postmenopausal women. We conducted a systematic literature review about the effects of (1) HIV infection on age at menopause and (2) menopause on antiretroviral therapy (ART) response, in order to inform optimal treatment strategies for menopausal women living with HIV infection. We used the Ovid Medline database from 1980 to 2012. We included studies that focused on HIV-infected persons, included postmenopausal women, and reported outcome data for either age at menopause or response to ART across menopause. We identified six original research articles for age at menopause and five for response to ART across menopause. Our review revealed that current data were conflicting and inconclusive; more rigorous studies are needed. Disentangling the effects of menopause requires well-designed studies with adequate numbers of HIV-infected and HIV-uninfected women, especially disproportionately affected women of color. Future studies should follow women from premenopause through menopause, use both surveys and laboratory measurements for menopause diagnoses, and control for confounders related to normal aging processes, in order to inform optimal clinical management for menopausal women living with HIV.